Analisis Framing Berita Kasus Tuduhan Pelanggaran UU Informasi dan Transaksi Elektronik (UU ITE) terhadap TikTokers Bima Kritik Lampung di Media Online Detik.com dan Kompas.com - Muhammad Iqbal (MEDIALOG: Jurnal Ilmu Komunikasi, 2023)
Social media provides freedom of opinion and expression for its users. In Indonesia, the use of social media is regulated in the 2008 ITE Law. This study examines the reporting of one of the ITE Law controversy cases in the form of accusations of hate speech containing SARA against Bima Yudho Saputro who criticized Lampung as "Dajjal". The purpose of this study is to find out how the media Detik.com and Kompas.com in framing news cases of alleged violations of the ITE Law using Robert N. Entman's framing device. This research includes framing analysis research with qualitative approach methods. The results of this study are seen from the Define Problem framing tool, the media Detik.com and Kompas.com trying to define cases of alleged violations of the ITE Law by Bima as cases that do not need to be brought into the realm of law, evidenced by headlines that tend to write responses from several parties. Diagnose Causes, a framing developed by Detik.com and Kompas.com media is a report of violations of the ITE Law against Bima. Make Moral Judgement, it is seen Detik.com highlight the statement of the family responding to the case as a lesson for various parties, while Kompas.com highlight statements from various parties who consider the report against Bima to be a criminalization of human rights and a violation of democratic values. Treatment Recommendation, Detik.com and Kompas.com highlight the resolution of existing problems by writing down the attitude of the Lampung Regional Police regarding the Bima case.